MENINGKATKAN PARTISIPASI MASYARAKAT DALAM PESTA PANEN UNTUK MENDORONG KEBERLANJUTAN PERTANIAN LOKAL DI KABUPATEN BARRU - Hartati, Hartati; Maslan, Maslan; S, Yunita (Gapenas Publisher, 2024)
The harvest party is a long-standing tradition in Barru Regency, which is not only a moment to celebrate agricultural products, but also as a means to strengthen social relations within the farming community. However, community participation in this activity still faces various challenges, especially related to the lack of awareness of the importance of their role in supporting the sustainability of local agriculture. This article aims to analyze the factors that influence community participation in the harvest festival and develop strategies to increase their involvement in efforts to encourage agricultural sustainability in Barru Regency. This research uses a descriptive qualitative method with a participatory approach, involving in-depth interviews, participatory observation, and documentation related to the harvest festival. The research results show that increasing community participation can be achieved through intensive education and outreach, empowering the younger generation, as well as stronger collaboration between the government, farmers and related institutions. The harvest festival not only functions as a cultural activity, but also as a medium for introducing sustainable agricultural technology, so that it can encourage increased welfare of farmers and preserve local agriculture. Based on these findings, it is recommended that harvest festival managers in Barru Regency increase event promotion, strengthen the involvement of the younger generation, and develop educational programs that focus on sustainable agriculture